Optimalisasi Peta Pengendalian Penduduk untuk Diintegrasikan pada Organisasi Perangkat Daerah (OPD) di Kabupaten Bandung Barat - putri, edsryan puspadianis Ramitha Satya; Istambul, Muhammad Rozahi (Universitas Andalas, 2020)
Demographic maps can present statistical data on demographic education levels, population stages, family stages, education levels, age, and number of lives in families based on participation in the National Health Insurance (JKN). Where every Regional Apparatus Organization (OPD) in West Bandung Regency that requires population control data needs a data integration and performance optimization, so that in each Regional Apparatus Organization (OPD) in work there is no more duplication of work. In this study, it is expected to be able to map all information about population control data to help the community and Regional Apparatus Organizations (OPD) in West Bandung Regency in order to obtain information clearly from population control data based on the results of family data collection which will make it easier for Regional Apparatus Organizations (OPD) related in order to help the entire community in West Bandung Regency. In this case a solution will be made by utilizing the QGIS application in solving problems where for population control maps can be integrated in the Regional Apparatus Organization (OPD) in West Bandung Regency.